Nigeria - Towards the Improved Delivery of Social Services - Woo, Josephine (World Bank, Washington, DC, 2012)
Nigeria possesses a wealth of natural resources including major oil and gas deposits, a variety of solid minerals, good agricultural land, a well developed industrial base, an extensive banking system, a large labor force, and a vibrant private sector. However, the country's tremendous potential for growth and development has yet to be fulfilled. Real income and consumption per capita today are scarcely higher than they were in 1971 before the start of the oil boom. Social indicators have been improving somewhat but remain far acceptable levels. There is an urgent need to put in place, over the medium term, mechanisms that will ensure sustained improvements in the quality and quantity of social services.